Dark academia how universities die - Fleming, P. (Peter) 1972- (London Pluto Press, 2021)
Fleming delves into the metrics-obsessed, overly hierarchical world of academia to bring out the hidden underbelly of the neoliberal university. He examines commercialisation, mental illness and self-harm, the rise of managerialism, students as consumers and evaluators, and the competitive individualism which casts a dark sheen of alienation over departments. Arguing that time has almost run out to reverse this decline, this book shows how academics and students need to act now if they are to begin to fix this broken system.
Introduction: Infinite hope ... but not for us -- Dark academia -- La La Land -- Welcome to the edu-factory -- The authoritarian turn in universities -- You're not a spreadsheet with hair -- The demise of homo academicus -- High impact ... -- The academic star-complex -- Student hellscapes -- How universities die -- Conclusion: Are some lost causes truly lost?
Includes bibliographical references (pages 166-201) and index.
Keywords: Neoliberalism; Universities and colleges; Universities and colleges -- Faculty -- Psychology; Néo-libéralisme.; Universités.; Universités -- Corps enseignant -- Psychologie; colleges (institutions); universities (institutions); Neoliberalism; Universities and colleges; Universities and colleges -- Faculty -- Psychology